Sex Differences in Peripheral Augmentation Index and Arterial Reservoir Pressure during Upper Limb Postural Shifts. (5th January 2014) - Heffernan, Kevin S.; Kasprowicz, Ari G.; Tarzia, Brendan J.; Davies, Justin E.; Casey, Darren P.
Abstract : We examined the peripheral hemodynamic response to passive arm postural changes in young men and women. Radial artery pulse waveforms were captured using applanation tonometry in 20 men (age 27 ± 2 yrs, BMI 25 ± 1 kg/m 2 ) and 20 women (age 27 ± 2 yrs, BMI 23±1 kg/m 2 ). Arm position was maintained at either heart level or supported 14 cm above/below heart level in a randomized fashion. Systolic augmentation index (sAIx) and diastolic augmentation index (dAIx) were used as estimates of pressure from wave reflections arriving in systole and diastole, respectively. A novel reservoir-wave separation technique was used to obtain arterial reservoir pressure (pressure generated by arterial capacitance). Women showed a significant reduction in radial diastolic pressure-time integral (DPTI) (P < 0.05 ) and reservoir pressure (P < 0.05 ), with no change in peripheral sAIx (P > 0.05 ) or dAIx (P > 0.05 ) when moving the arm from below to above heart level. Conversely, men showed an attenuated change in radial DPTI (P > 0.05 ) concomitant with significant increases in reservoir pressure (P < 0.05 ), sAIx (P < 0.05 ), and dAIx (P < 0.05 ). Gravity-mediated changes in regional hemodynamics produced by passive arm postural shifts are sex specific. Men demonstrate less change in regional diastolic pressure concomitant with increased augmentation index and arterial reservoir pressure.